SISTEM PENGELOLAAN BARANG BUKTI DAN BARANG RAMPASAN DI KEJAKSAAN NEGERI JAKARTA UTARA PADA LINGKUP KEJAKSAAN REPUBLIK INDONESIA - Tirayudi, Jemmy Novian; Nurati, Dian Esti; Wangi, Maya Sekar (JI@P, 2020)
The objective of research is to study and to analyze the evidence and lootmanagement system in North Jakarta District Attorney in Republic of Indonesia?sAttorney Scope. Organization development at North Jakarta District Attorneylevel in Republic of Indonesia?s Attorney Scope has not been supported by thepresence of stipulation in the form of Standard Operating Procedure inimplementing the duty and function of evidence and loot management system, sothat the implementation of such duty and function has not run optimally eitherstructurally or hierarchically leading to vulnerability to internal conflictoccurring in the organization recalling the evidence and loot management sectionin North Jakarta District Attorney refers to an internal consensus of organizationonly in implementing its duty and function.The result of research showed that, viewed from organizational managementfunction, the evidence and loot management system in North Jakarta DistrictAttorney in Republic of Indonesia?s Attorney Scope, involving planning,organization, activation, and coordination, indicates the presence of planning instructural development not supported with operational stipulation in the form ofstandard operating procedure. Then, its structural organization has notfunctioned optimally in its hierarchy in the implementation of authority andresponsibility, while in the term of activation, it can be seen the leadership thatuse its discretion in looking for the solution to the implementation of duty andfunction in evidence and loot management section and the coordination in thestructure in North Jakarta District Attorney has not set forth the equality principlein structure, because the role of structure has not been seen clearly, but there iscoordination at bottom level, so that the form of responsibility in hierarchy levelis still vulnerable to the internal conflict by blaming each other.